French object clitics in sequential versus simultaneous bilingual acquisition - Strik, Nelleke; Pérez-Leroux, Ana Teresa; Pirvulescu, Mihaela; Roberge, Yves (Linguistica Atlantica, 2015)
In this short exploratory study we investigate the production of French object clitics in sequential bilingual acquisition, and determine whether the observed patterns are similar to those in simultaneous bilingual acquisition. A picture elicitation task was used with 11 Anglophone children learning French (mean age 4;09) and 11 age-matched English-French simultaneous bilinguals, as well as 11 aged-matched monolingual French children. No errors in clitic placement were found in the sequential group, in line with previous results from older children. In both bilingual groups, the majority of responses were null objects (more than 60%). It appeared that children with a later age of onset and shorter exposure to French did in fact perform similarly to bilingual children who acquired French from birth. The high number of object omissions suggests a quantitative effect when compared to monolingual Francophone children. We propose that this delay is due to the retention of a default null object representation.